Coexisting Attractors In A Autonomous 4ᵗʰ Order, Non Linear, Electric Circuit - Stouboulos, Ioannis N. (İstanbul Kültür Üniversitesi Yayınları, 2006)
In this paper we have studied the dynamic behavior of a non driven electric circuit of 4th order with two active elements, one linear negative conductance & one non linear resistür ofN-type exhibiting a symmetrical piecewise linear v-i characteristic. The resistor Ri serves as the control parameter of the system. We have observed formation of "bubbles" for some initial conditions. In a narrow region of Ri values what has been observed is antimonotonicity in the bifurcation diagram, different routes to chaos via period doubling sequences and reverse period doubling and transition from periodic to quasi-periodic and finally to chaos. We have also studied the dependence of circuit behavior on the initial conditions.
Keywords: bubbles; coexisting attractors; antimonotonicity; chaos; period doubling; kabarcıklar; çekicilerin eşlik; iki kat dönemi